Dysproteinemia-Associated Kidney Disease: A Single-Center Observational Study - João Bernardo; João Oliveira; Filipe Marques; Joana Gameiro; Cristina Outerelo; Estela Nogueira; Sofia Jorge; José António Lopes (Publicações Ciência e Vida, 2022)
Introduction: Dysproteinemia is associated with kidney damage and treatment of underlying conditions is crucial to minimize kidney damage. The aim of this study was to describe and analyze the characteristics and outcome of the patients diagnosed with dysproteinemia-associated kidney disease with initial renal presentation. Methods: We performed a retrospective observational study of the patients admitted with initial dysproteinemia-associated kidney disease in the Department of Nephrology and Renal Transplantation at Centro Hospitalar Universitário Lisboa Norte in Lisbon over five years. Results: Thirty patients were diagnosed with dysproteinemia-associated kidney disease: twenty-six (86.7%) with multiple myeloma, one of these with concomitant amyloidosis; three (10.0%) with gammopathy of renal significance and one (3.0%) with Waldenström macroglobulinemia. Mean age was 71.5 (± 12.44) years and half patients were male. Anemia, hypercalcemia, hyperphosphatemia, and hypoalbuminemia was found in twenty-three (76.7%), ten (30.0%), fourteen (46.7%) and seventeen (56.7%) patients, respectively. Bence Jones proteinuria was found in twenty-one (70.0%) patients and thirteen (43.3%) patients presented with creatinine >6 mg/dL. Twelve (40.0%) patients were submitted to kidney biopsy and light chain cast nephropathy was the most common finding. Twenty-nine (96.7%) patients were treated with chemotherapy. Twenty-two (72.3%) patients required renal replacement therapy and six of these (27.3%) patients were submitted to high cut-off dialyzers. Four (13.3%) patients had full recovery of renal function, sixteen (53.3%) remained dialysis-dependent at hospital discharge. At one-year follow-up, eleven (36.7%) patients remained dialysis-dependent and six (20.0%) had died. Conclusion: Dysproteinemia-associated kidney disease can present heterogeneously, and diagnostic suspicion is crucial to start prompt directed therapy to improve kidney and overall outcomes. Renal replacement therapy requirement and dependence at discharge appear to be related to higher mortality in these patients. In the future, routine screening of dysproteinemia may be particularly relevant in older patients to prevent irreversible kidney damage.